Journey to the end - Mann, Greyson (Mann, Greyson. Secrets of an overworld survivor, 2018)
Will has found a set of Elytra wings, but he won't use them until he can find a second set for his friend Mina. Together, they set out for the End, where they must face Endermen, shulkers, and the fierce Ender Dragon to find the wings -- and make it home again--